A Long-Term Dynamic Analysis of Heat Pumps Coupled to Ground Heated by Solar Collectors - Vincenzo Ballerini; Eugenia Rossi di Schio; Paolo Valdiserri; Claudia Naldi; Matteo Dongellini (Applied Sciences, 2023)
In agreement with the decarbonization of the building sector to meet the 2050 climate neutrality targets, borehole thermal storage for solar energy represents a potential solution to increase the energy efficiency of renewable energy plants. As is well known, electricity is not the optimum solution to integrate large inflows of fluctuating renewable energy. In the present paper, we investigate the possibility to use the solar collector to give energy to the borehole field. In detail, a solar-assisted geothermal heat pump is applied to a school located in Milan, Italy. In winter, both the energy from the solar collector and the heat pump are collected into a storage tank connected to the emission terminals, whereas, in summer, as there is no energy demand, the hot water from the solar collector flows into the geothermal probes. By means of this seasonal thermal energy storage technology, the intermittent solar energy collected and stored during the summer months can be utilized during the winter months when the heating demand is high. A long-term dynamic analysis is performed by employing Trnsys. The results show that solar collectors coupled with ground-source heat pumps can give an important contribution to the soil temperature drift, and this also applies in cases of un-balanced loads during the heating season. Moreover, the employment of solar collectors increases the seasonal coefficient of performance of the heat pumps and may rise to reductions to the probes field.